Eupraxia, A Step Toward A Plasma-Wakefield Based Accelerator With High Beam Quality. (November 2019) - Nghiem, P A P; Alesini, D; Aschikhin, A; Assmann, R W; Audet, T; Beck, A; Chance, A; Chen, M; Chiadroni, E; Cianchi, A; Clarke, J A; Couprie, M E; et al.
Abstract: The EuPRAXIA project aims at designing the world's first accelerator based on advanced plasma-wakefield techniques to deliver 5 GeV electron beams that simultaneously have high charge, low emittance and low energy spread, which are required for applications by future user communities. Meeting this challenging objective will only be possible through dedicated effort. Many injection/acceleration schemes and techniques have been explored by means of thorough simulations in more than ten European research institutes. This enables selection of the most appropriate methods for solving each particular problem. The specific challenge of generating, extracting and transporting high charge beams, while maintaining the high quality needed for user applications, are being tackled using innovative approaches. This article highlights preliminary results obtained by the EuPRAXIA collaboration, which also exhibit the required laser and plasma parameters.